STUDY OF CONSUMER BEHAVIOR RESEARCH TO MEASURE PURCHASE DECISION AND EFFECTIVENESS OF MARKETING MIX IN NU SWALAYAN - Rozieqy, Ahmad; Al-Manuri, Aqil Husein (Reinforce: Journal of Sharia Management, 2025)
The number of retail businesses in Sumenep Regency and low levels of community income are a problem for every business actor. Business actors must be innovative in their strategies to attract more consumers. Through the study of consumer behavior, this research aims to determine the level of people's purchase decision-making towards NU self-service. It also aims to determine the effectiveness of the marketing mix used by NU supermarkets. This study uses a mixed-methods approach, namely qualitative and quantitative methods, to obtain more complete information. This study used the Lemeshow formula to determine the sample size because the population size was unknown. Ninety-six respondents were combined to yield 150 respondents for more comprehensive information. The result of this study is that consumer behavior significantly affects consumer purchasing decisions towards NU supermarkets. In addition, consumer behavior research indicates that NU self-service's marketing mix is highly effective.